THE IMPACT OF THE ZAHOURIK MODEL ON THE DEVELOPMENT OF CONTEMPLATIVE THINKING AMONG STUDENTS OF THE COLLEGE OF PHYSICAL EDUCATION AND SPORTS SCIENCE - Ali Yahya Majeed; Assist. Prof. Dr. Zeyad Salim Alqarani (American Journals, 2023)
The research aims to:- Identify the impact of the Zahourik model on the development of contemplative thinking among third-year students in the College of Physical Education and Sports Science.- Identify the differences between the results of the two post-tests for the experimental and control groups in the development of contemplative thinking among third-year students in the College of Physical Education and Sports Science.The researchers assumed the following:- There are statistically significant differences between the students' scores in the pre-test and post-test for the experimental group in favor of the post-test in developing contemplative thinking.- There are no statistically significant differences between the students' scores in the pre-test and post-test for the control group in developing contemplative thinking.- There are statistically significant differences between the students' scores in the post-test for the experimental group and the control group in favor of the experimental group in developing contemplative thinking.The researchers used the appropriate experimental method for the nature and problem of the research. The research population consisted of third-year students in the College of Physical Education and Sports Science, Tikrit University, for the academic year (2022-2023), totaling 128 students distributed across three sections. The experimental group was randomly selected from Section (D), consisting of 42 students, and Section (C) was the control group, consisting of 43 students. Section (B) with 43 students was excluded, and absent students were also excluded, resulting in each research group consisting of 25 students.
Keywords: model, teaching methods, reflective thinking, development, Cognitive attainment